Integrasi Kurva Horizontal To Vertical Spectral Rasio (Hvsr) dan Kurva Eliptisitas Gelombang Rayleigh untuk Penentuan Indeks Kerentanan Seismik (Kg): Sains - Sujabar, Sujabar; Adhi, M. Aryono; Muzli, Muzli; Sofian, Sofian; Fatoni, Iza (Jurnal Pendidikan Matematika : Judika Education, 2025)
This study aims to determine the seismic vulnerability index using microtremor data in Parigi City. A microtremor survey was conducted at 81 sites across the city. The data were analyzed to obtain the Horizontal to Vertical Spectral Ratio (HVSR) curve and the Rayleigh wave ellipticity curve. These two curves were combined to derive the dominant frequency (f₀) and amplification factor (A₀). The Rayleigh wave ellipticity curve was used to guide the determination of the dominant frequency (f₀) and amplification factor (A₀) on the HVSR curve. The results were then used to calculate the seismic vulnerability index (Kg). The peak of the Rayleigh wave ellipticity curve (Aₑₗₗ) can assist in identifying the dominant frequency (f₀), both when the A₀ peak is clearly visible (clear peak) and when there are multiple or unclear peaks. The use of Aₑₗₗ also helps refine the determination of A₀ values, yielding more stable results. The final mapping results show that the dominant frequency values range from 0.26 Hz to 2.9 Hz, the amplification factor ranges from 1.61 to 4.77, and the seismic vulnerability index ranges from 1.47 to 113.59. Conclusion, The integration of the HVSR curve and the Rayleigh wave ellipticity curve carried out in this study shows that both can be combined and complement each other.   Keywords: Dominant Frequency (f0), Amplification Factor (A0), Seismic Vulnerability Index (Kg), Rayleigh Wave Ellipticity Curve, Horizontal-to-Vertical Spectral Ratio (HVSR) Curve